Dynamics of Maintaining Religious Harmony in Ambon City, Maluku Province - Yunus Rahawarin (West Science Social and Humanities Studies, 2023)
This study aims to investigate the factors that have played a key role in maintaining religious harmony in the city of Ambon, Maluku. Despite its history of sectarian conflicts in the past, Ambon managed to create an environment that supported inter-religious harmony. This research uses a qualitative approach with in-depth interviews and content analysis of relevant primary and secondary sources. The results showed that the history of harmony in Ambon became a strong foundation for building harmony today. Interfaith dialogue is regularly held, providing a platform for religious and community leaders to share understanding and celebrate diversity. The active involvement of the community in joint religious events is also a key element in forming unity amid differences. Inclusive religious education and the role of religious leaders in promoting the message of peace are significant factors in shaping tolerance among Ambonese people. An education system that introduces the values of tolerance early on helps create a generation that values diversity. Despite its success, the study also highlights the challenges Ambon faces in maintaining harmony, especially related to the impact of globalization and social change. However, the spirit of mutual cooperation and mutual commitment continues to be the main driver in efforts to maintain religious harmony in Ambon. This research contributes to our understanding of social dynamics and key factors that can support the development of a harmonious society amidst religious diversity. The implications of these findings can be used as a basis for the development of policies and programs that are more effective in maintaining religious harmony across a variety of social contexts.